A Review of Literature and Article on Importance of Nidan Panchak Ayurveda - Aman, Mulani; Prakash, Mane; Sachin, Rohani; Mangesh, Udmale (International Journal of Complementary Medicine, 2022)
Nidana Panchaka is one of Ayurveda's several diagnostic procedures. It is the most significant way for determining the source of an illness, as well as predicting its prognosis. Nidana Panchaka comprises of five items which are Nidana (etiological factors), Purvaroopa (primordial symptoms), Roopa (signs and symptoms), Upashaya (like and dislike) and Samprati (etiopathogensis) (etiopathogensis). Diagnosis of sickness depends on Tridoshas which are Vata, Pitta, Kapha which are responsible for any disease that arises in the body. These imbalances in the Doshas of the body are caused by etiological variables such as a person's lifestyle and eating habits. Prior to seeking therapy for a condition, a proper diagnosis is required. There are numerous additional procedures for diagnosing the ailment, such as Ashtavidha Pareeksha, Dashavidha Pareeksha, and Chaturvidha Pareeksha, but the focus of this article is on the significance of Nidana Panchaka.
Keywords: Nidanpanchak; ayurveda; diagnostic